Analisa Teknis Penetapan Kanal Frekuensi Radio Untuk Lembaga Penyiaran Radio Komunitas Wilayah Kabupaten Batang - jayati, Ari endang; Minarti, Wahyu; Heranurweni, Sri (P3M Politeknik Negeri Banjarmasin, 2021)
The radio frequency spectrum constitutes a limited and strategic natural resource with high economic value, so it must be managed effectively and efficiently to obtain optimal benefits by observing national and international legal principles. Radio Community Broadcasting Institution uses limited frequency allocation in three channels, namely, in the frequency channels 202 (107.7 MHz), 203 (107.8 MHz), and 204 (107.9 MHz), with limited transmit power and area coverage. The problem in this research is the frequency overlap with other community radios in an area. The issue raised is whether it is possible to establish a new community radio in the Batang Regency area by paying attention to existing radios that have licenses in districts/cities that are in the area directly adjacent to Batang Regency by considering the limited allocation of radio frequency channels community, without the occurrence of radio frequency interference with other community radios. The purpose of this research is to solve these problems. It is necessary to have a policy in determining radio frequency users to get good quality radio broadcast reception. The method used is to analyze the frequency determination technique based on the interference analysis on other community broadcasters. By using the Radio Mobile Software for frequency repetition simulation, in this research, the results show that Batang FM Community Radio does not allow to get frequency channels for community radio operations. After all, it interferes with the Service Area of ​​Soneta FM Radio in Pekalongan City because it does not meet the requirements for determining the frequency channel = Eu> NF, namely the Nuisance Field (NF) value of 109.7 dB is greater than the Minimum Usable Field strength (Eu) of 66 dB. In comparison, Limpung FM Radio gets radio frequency on channel 203 (frequency 107.8 MHz) because it meets the requirements for determining the frequency channel = Eu> NF, namely the Minimum Usable Field strength (Eu) 66 dB greater than the Nuisance Field (NF) of 55.7 dB.